Spontaneous Abdominal Bleeding from an Infundibulopelvic Ligament Tear in a Patient with Large Ovarian Fibroma - Justin To; Cui-lan Li (Case Reports in Obstetrics and Gynecology)
Ovarian fibromas are rare benign solid tumors of the ovary which are often difficult to differentiate from uterine leiomyomas preoperatively. The symptoms usually include abdominal discomfort and may have ascites and/or an elevation in CA-125 levels. There have been no publications of associated abdominal bleeding to date. The treatment is surgical removal via a laparoscopic or laparotomic approach. We present a case of a 19 cm unilateral ovarian fibroma with abdominal bleeding from a spontaneous right infundibulopelvic ligament (IPL) tear who underwent a laparoscopic and mini-laparotomic right salpingo-oophorectomy. Patients with large ovarian fibromas should be cautioned that abdominal bleeding and/or acute abdominal pain can occur and that a minimally invasive surgical approach is feasible.